The Burkill-Cesari Integral on Spaces of Absolutely Continuous Games - F. Centrone; A. Martellotti (International Journal of Mathematics and Mathematical Sciences)
We prove that the Burkill-Cesari integral is a value on a subspace of AC and then discuss its continuity with respect to both the BV and the Lipschitz norm. We provide an example of value on a subspace of AC strictly containing pNA as well as an existence result of a Lipschitz continuous value, different from Aumann and Shapley’s one, on a subspace of AC∞.